Mild Hyperhomocysteinemia and Low Folate Concentrations as Risk Factors for Cervical Arterial Dissection - Arauz, Antonio; Hoyos, Leticia; Cantú, Carlos; Jara, Aurelio; Martínez, Leticia; García, Irma; Fernández, María de los Ángeles; Alonso, Elisa (Cerebrovascular diseases (Basel, Switzerland), 2007)
Background and Purpose: Elevated homocysteine (Hcy) plasma levels are associated with an increased risk of spontaneous cervical artery dissection (sCAD). We examined the potential association between Hcy, folate, vitamin B 12 levels and 5,10-methylenetetrahydrofolate reductase (MTHFR) polymorphisms in patients with cerebral infarct caused by sCAD. Patients and Methods: 39 patients who survived a cerebral infarct caused by sCAD [20 (51%) women; 24 (61.5%) vertebral and 15 (38.5%) internal carotid arteries], and 76 healthy control subjects were included. Hcy plasma levels (fasting and after methionine load), folate and vitamin B 12 levels were measured. We also performed polymorphisms of MTHFR. Hcy, vitamin B 12 , folates and polymorphisms of MTHFR were assessed and any associations were analyzed using multivariate statistics. Results: Mean plasma fasting Hcy level was 9.81 µmol/l for cases and 6.38 for controls (p = 0.001). The occurrence of sCAD was associated with elevated fasting Hcy levels (>95th percentile over the control group) with an adjusted odds ratio of 7.9 (95% CI 1.66–35). The association between low plasma folate values (<5th percentile) and the presence of CAD was 7.9 (95% CI 1.6–31) after adjusting for confounding variables. The distribution of the MTHFR genotype showed a higher TT mutant frequency among CAD patients (p = 0.034). Conclusions: High plasma concentrations of Hcy and low plasma levels of folate were associated with an increased risk of sCAD in the sample studied. We conclude that deficiencies in nutritional status may contribute to the relatively high incidence of CAD in Mexico.